SAGRARIO Y MANIFESTADOR EN EL RETABLO BARROCCO ESPAÑOL - Martín González, J.J. (Imafronte, 1997)
The altarpiece appenred as didactic iconography placed behind the main altar. But the valomtion that the Council of Trent gave to the Eucharist made this the predominant objective in the baroque period. Sheme, monstrance and tabeinacle are usually terms equivalent to the place where the sacred forms are kept. But the tabernacle has an additional meaning: momentality, It has the shape of a tower; the upper part is the monstrance, a transparent recipient in which the sucred form is placed for everlasting worship. The form is visible in the monstrance that is generally presented in a theatrical manner (scene), with a small curtain or revolving body. The altarpiece is part of the theatrical scenery, which helps to create more emotion when the holy sacrament is shown.